Effectiveness of a videoconferencing group-based dyad acceptance and commitment therapy on the quality of life of chronic heart failure patients and their family caregivers: A study protocol for a randomized controlled trial - Zhang, Xuelin; Ho, Grace W. K.; Mak, Yim Wah (PloS one, 2024)
Chronic heart failure (CHF) poses a significant burden on both patients and their family caregivers (FCs), as it is associated with psychological distress and impaired quality of life (QOL). Acceptance and Commitment Therapy (ACT) supports QOL by focusing on value living and facilitates acceptance of psychological difficulties by cultivating psychological flexibility. A protocol is presented that evaluates the effectiveness of a dyad ACT-based intervention delivered via smartphone on QOL and other related health outcomes compared with CHF education only. This is a single-center, two-armed, single-blinded (rater), randomized controlled trial (RCT). One hundred and sixty dyads of CHF patients and their primary FCs will be recruited from the Cardiology Department of a hospital in China. The dyads will be stratified block randomized to either the intervention group experiencing the ACT-based intervention or the control group receiving CHF education only. Both groups will meet two hours per week for four consecutive weeks in videoconferencing sessions over smartphone. The primary outcomes are the QOL of patients and their FCs. Secondary outcomes include psychological flexibility, psychological symptoms, self-care behavior, and other related outcomes. All outcomes will be measured by blinded outcome assessors at baseline, immediately post-intervention, and at the three-month follow-up. Multilevel modeling will be conducted to assess the effects of the intervention. This study is the first to adopt an ACT-based intervention for CHF patient-caregiver dyads delivered in groups via smartphone. If effective and feasible, the intervention strategy and deliverable approach could be incorporated into clinical policies and guidelines to support families with CHF without geographic and time constraints. ClinicalTrials.gov Identifier: NCT04917159. Registered on 08 June 2021.